Snapshot of MRI neural axis abnormalities seen in consecutive cohort of pediatric and young adult patients undergoing spinal deformity correction in tertiary care hospital setting in Pakistan (Journal of Pakistan Orthopaedic Association, 2020)
TitleSnapshot of MRI neural axis abnormalities seen in consecutive cohort of pediatric and young adult patients undergoing spinal deformity correction in tertiary care hospital setting in PakistanAshfaqAhmed , Abdullah Shah , Majid Zaheer,Ammar Dogar , RizwanAkram , Amer AzizIntroduction            The pre-operative use of MRI to identify occult intraspinal anomalies before surgical correction of paediatric spinal deformity contributes  widely accepted best practice recommendations. However due to economic and resource constraints these recommendations are not universally implemented in many health-care settings. Study was conducted to document the frequency and types of encephalomyelonic Axis Anomalies found in a consecutive cohort of paediatric and young adult patients undergoing spinal deformity surgery with the aim of consolidating the case for pre-operative MRI imaging of all surgical patients.Methods            Departmental prospective database used to identify consecutive paediatric and young adult patients undergoing scoliosis correction between January 2015 and December 2018 at a tertiary spine referral center in Pakistan. Data collected on clinical and MRI findings. Clinical data included age, sex, scoliosis type (idiopathic, congenital, neuromuscular & syndromic) and presence of abnormal neurological findings. MRI data included presence and type of neural axis abnormalities (NAA). Results87 patients were included having the diagnosis of idiopathic and congenital scoliosis, and from these patients, 33.3% (n =29) were male, and the majority were female patients as 66.7% (n=58) diagnosed with a different type of scoliosis (Idiopathic or congenital) with an average age of 13.7±3.87 ranged from (4-27) years.   Idiopathic  and congenital scoliosis were found as 56 ( 64.4% )  and  31 (35.6 % )  respectively. Considering divergent anomlies , Diastomyelia was documented in 4 (04.59 %) .likewise ,Tethered Cord in 2 ( 2.29 % ) patients  , 10 ( 11.49 %  )   of patients had Syringomyelia  and Chiari Malformations was noticed in  2 ( 2.29 % ) patients.  Lipoma and diplomyelia was not screened in single patient. However,  2 (2.29% ) was having dural fault, conus 9 ( 10.34 % )  and 1 (1.15% ) foramen magnum compression.When rare anomalies were viewed ,Hydromyelia was detected in 3 (3.44 % ), tonsillar ectopia in 2 (2.29% )  and OS Odontoideum in 1(1.14% ).Moreover,only 5 (5.74% ) of patients having neurology involved while  other were having intact neurology.Conclusion ;Patients with scoliosis having discrete anamolies that can be missed  on clinical examination and X-rays. Pre operative Magnetic Resonance Imaging has  vital role  to identify  these peculiar abnormalities  in these patients before considering  any surgical intervention.